1982
DOI: 10.1128/jb.149.2.440-448.1982
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of acetyl coenzyme A from carbon monoxide, methyltetrahydrofolate, and coenzyme A by enzymes from Clostridium thermoaceticum

Abstract: Two purified fractions from Clostridium thermoaceticum are shown to catalyze the following reaction: CO + CH3THF + CoA ATPCH3COCoA + THF. The methyltetrahydrofolate (CH3THF) gives rise to the methyl group of the acetylcoenzyme A (CoA) and the carbon monoxide (CO) and CoA to its carboxyl thio ester group. The role of ATP is unknown. One of the protein fractions (F2) is a methyltransferase, whereas the other fraction (F3) contains CO dehydrogenase and a methyl acceptor which is postulated to be a corrinoid enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(52 citation statements)
references
References 38 publications
0
52
0
Order By: Relevance
“…Resolution of enzmes required for synthesis of acetyl-CoA from pyruvate and methyltetrahydrofolate (Drake et al 253 ) 1981-1982 Demonstration that CO replaces the carboxyl-group of pyruvate and undergoes an exchange reaction with acetyl-CoA (Drake et al, 254 Hu et al 61 ) 1982…”
Section: Acetyl-coa Wood-lungdahl Pathway: Evolution Fixation Of Carmentioning
confidence: 99%
See 1 more Smart Citation
“…Resolution of enzmes required for synthesis of acetyl-CoA from pyruvate and methyltetrahydrofolate (Drake et al 253 ) 1981-1982 Demonstration that CO replaces the carboxyl-group of pyruvate and undergoes an exchange reaction with acetyl-CoA (Drake et al, 254 Hu et al 61 ) 1982…”
Section: Acetyl-coa Wood-lungdahl Pathway: Evolution Fixation Of Carmentioning
confidence: 99%
“…Acetyl-CoA synthase not only catalyzes the reduction of CO 2 to CO and the synthesis of acetyl-CoA as shown in FIGURE 5, but can also oxidizes CO to CO 2 ; this latter reaction is the historical basis for referring to acetyl-CoA synthase as CO dehydrogenase. [58][59][60][61][62] It is now understood that the different subunits of acetyl-CoA synthase are capable of catalyzing different reactions. The enzymological features of the acetyl-CoA pathway that was resolved from M. thermoacetica can be found in several reviews and articles.…”
Section: Acetyl-coa Wood-lungdahl Pathway: Evolution Fixation Of Carmentioning
confidence: 99%
“…The CO-DH from anaerobes contains Ni and Fe-sulfur centers [18], whereas that from aerobes contains Mo instead of Ni [19]. The importance of this enzyme in the metabolism of C. thermoaceticum became apparent when it was found that CO could replace pyruvate as a source of the carbonyl group of acetyl-CoA and that acetyl-CoA was synthesized from CH3THF, CoASH and CO [20]. At that time.…”
Section: Co + H:o ~ Co2 + 2h ' + 2ementioning
confidence: 99%
“…CO dehydrogenase was purified and confirmed to contain Ni [130]. Most important of all, they found that that fraction F 3 and fraction F2, the methyltransferase, catalyzed the formation of acetyl CoA from CO, CH3-H4folate and coenzyme A [131]. Thus, CO can replace pyruvate as the source of the carboxyl in the formation of acetate.…”
Section: Acetate Synthesis Via the Acetyl Coa Pathway: Historical Permentioning
confidence: 99%
“…Before the discovery that acetyl CoA could be synthesized from CO and CH3-H4folate [131], acetate synthesis could only be studied from pyruvate and CH3-H4folate (reaction 6b) in a complex assay [108]. The system became much simpler when acetyl CoA or acetyl phosphate formation from CO, CH3-H4folate, CoA, and ATP was demonstrated.…”
Section: Methyltransferase and Corrinoid Proteinmentioning
confidence: 99%